Corporate Liability of Ride-Hailing Services: An Analysis of Partnership Legal Fiction and the Reconstruction of Passenger Safety Regulation - Mariyam, Siti; Mulyani, Sri; Saryana, Saryana (SIGn Jurnal Hukum, 2025)
The rapid adoption of ride-hailing services in Indonesia is confronted by the problem of passenger safety vulnerability, stemming from normative regulatory insufficiency. The prevailing legal framework, comprising both the lex generalis (Law Number 22 of 2009) and the lex specialis (Ministerial Regulation Number 118 of 2018), is found to fail to provide a precise and operational mechanism for corporate liability. This failure creates a significant regulatory gap. This research aims to analyze the insufficiency of this legal framework, deconstruct the juridical implications of the “partnership” status, and construct an ideal, justice-based liability model. Employing a normative legal research (juridical-normative) method with statute, conceptual, and historical approaches, this study analyzes primary and secondary legal materials. The research findings indicate that this regulatory gap is exploited by application companies through the “partnership” construction. Substantively, this construction constitutes a legal fiction and a disguised employment relationship. This strategy is used to evade the doctrine of vicarious liability and systematically contributes to human error, which is the primary cause of accidents. This systematic contribution occurs through exploitative algorithmic management and the absence of fatigue management. Therefore, the novelty of this research is the proposition of a fundamental legal reconstruction. This reconstruction comprises two steps: imperatively affirming the legal status of application companies as “Transportation Service Providers,” and implementing four pillars of imperative liability mechanisms: comprehensive insurance, vehicle-worthiness standards, driver-welfare standards (including online-hour limits), and a rapid victim compensation mechanism.